1
$\begingroup$

This seem too simple that I cant even break this down..

Base case: For $n=1$, we have: LHS: $25^1=25$; RHS: $6^1$

So LHS$>$RHS, holds.

Inductive, hypothesis: Assume $25^k>6^k$ for some $n=k>=1$

Inductive step: We nee to show that $k+1$ holds, that is

$25^{k+1}>6^{k+1}$

from LHS:

$25^{k+1} = 25 * 25^k$

how do I continue from this, its already larger than $6^{k+1}$, however, how can I use what I already know?

$\endgroup$
  • $\begingroup$ 25*25^k > 25*6^k $\endgroup$ – user2879934 Dec 6 '15 at 2:51
6
$\begingroup$

As you said, we know $25^{k + 1} = 25^{k} \cdot 25$. Now, $25^{k} \cdot 25 > 25^{k} \cdot 6$, right? And by assumption, since $25^{k} > 6^{k}$, we have $25^{k} \cdot 6 > 6^{k} \cdot 6 = 6^{k + 1}$.

So, everything I said above is just: $$25^{k + 1} = 25^{k}\cdot 25 > 25^{k} \cdot 6 >6^{k} \cdot 6 = 6^{k + 1} $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.